Nanoparticles: A review on their synthesis, characterization and physicochemical properties for energy technology industry - Ahmad Tajuddin Mohamad, *; Kaur, Jesbains *; Nor Azwadi Che Sidik,; Saidur Rahman, * (Penerbit Akademia Baru, Johor, Malaysia, 2018)
In this paper, an overview about nanoparticles (NPs), their synthesis, characterizations, thermal properties and applications is discussed. Specific morphology, size and magnetic properties of NPs can be controlled by NP synthetic techniques. NPs have a size range of between 1-100 nm. This tiny structure will cause NPs to have a large surface area that correlates with their physical and chemical properties. They can be classified into different classes based on their properties, shapes or sizes. The different groups include fullerenes, metal NPs, ceramic NPs and polymeric NPs. The physicochemical properties of NPs are the main characteristics used in determining the specific functions among the various applications of NPs. Due to their characteristics; they are widely used in various applications including the energy technology industry, medical, imaging and environmental applications. However, some NPs have disadvantages such as environmental toxicities which will be taken into account for further improvements.